Bilirubin Links HO-1 and UGT1A1*28 Gene Polymorphisms to Predict Cardiovascular Outcome in Patients Receiving Maintenance Hemodialysis - Yang Ho; Tzen-Wen Chen; Tung-Po Huang; Ying-Hwa Chen; Der-Cherng Tarng (MDPI AG, 2021)
Serum bilirubin levels, which are determined by a complex interplay of various enzymes, including heme oxygenase-1 (HO-1) and uridine diphosphate-glucuronosyl transferase (UGT1A1), may be protective against progression of cardiovascular disease (CVD) in hemodialysis patients. However, the combined effect of HO-1 and UGT1A1*28 gene polymorphisms on CVD outcomes among hemodialysis patients is still unknown. This retrospective study enrolled 1080 prevalent hemodialysis patients and the combined genetic polymorphisms of HO-1 and UGT1A1 on serum bilirubin were analyzed. Endpoints were CVD events and all-cause mortality. Mean serum bilirubin was highest in patients with S/S + S/L of the HO-1 promoter and UGT1A1 7/7 genotypes (Group 1), intermediate in those with S/S + S/L of the HO-1 promoter and UGT1A1 7/6 + 6/6 genotypes (Group 2), and lowest in the carriers with the L/L HO-1 promoter and UGT1A1 7/6 + 6/6 genotypes (Group 3) (p < 0.001). During a median follow-up of 50 months, 433 patients developed CVD. Compared with patients in Group 3, individuals among Groups 1 and 2 had significantly lower risks for CVD events (adjusted hazard ratios (aHRs) of 0.35 for Group 1 and 0.63 for Group 2), respectively. Compared with the lower bilirubin tertile, the aHRs were 0.72 for the middle tertile and 0.40 for the upper tertile for CVD events. We summarized that serum bilirubin as well as HO-1 and UGT1A1 gene polymorphisms were associated with CVD among patients receiving chronic hemodialysis.